Fungicidal and plant growth-promoting traits of Lasiodiplodia pseudotheobromae, an endophyte from Andrographis paniculata - Segaran, Gayathri; Sathiavelu, Mythili (Frontiers in Plant Science, 2023)
Abstract Fungal endophytes are widespread and dwell inside plant cells for at least part of their life without producing any symptoms of infection. Distinct host plants may have different fungal endophyte rates and community compositions. Despite this, the endophytic fungi connected with the host plant and their hostile behaviors, remain unknown. The objective of the current research was to isolate and identify endophytic fungal species from the root of Andrographis paniculata. Endophytic fungal isolate APR5 showed higher inhibitory efficacy in dual and double plate assay against the tested phytopathogenic fungi. The scanning electron microscope analysis demonstrated that the phytopathogenic fungal hyphae were coiled by endophytes which makes them shrink and disintegrate. Further, an ethyl acetate crude extract effectively suppressed the mycelium growth of Rhizoctonia solani by 75 ± 0.1% in an agar well diffusion assay. The fungal isolate APR5 was identified as Lasiodiplodia pseudotheobromae using the nuclear ribosomal DNA internal transcribed spacer (ITS) region and qualitatively evaluated for their capacity to produce plant growth-promoting hormones. Gas chromatography-mass spectrometry was implemented to acquire a preliminary understanding of the secondary metabolic profile of ethyl acetate crude extract. 1-octadecene, erythritol, niacin, oleic acid, phenol, pantolactone, phenyl ethyl alcohol, p-cresol, and t-butyl hydroquinone are the metabolites analyzed in a crude extract of APR5 isolate and are reported to have antimicrobial properties. Keywords: Agriculture, Biocontrol agent, Chemical pesticide, Endophyte, Food production, Phytopathogenic fungi.